Femtosecond Stimulated Raman Spectroscopy. Issue 9 (20th April 2016) - Dietze, Daniel R.; Mathies, Richard A.
Abstract: The front cover artwork is provided by the group of Prof. Richard A. Mathies (University of California at Berkeley, USA). The image sketches the first step in vision: the 11‐ cis to all‐ trans isomerization of retinal in the visual pigment rhodopsin, as revealed by femtosecond stimulated Raman spectroscopy. Read the full text of the Review at10.1002/cphc.201600104 . Abstract : "Femtosecond stimulated Raman spectroscopy is a technology that enables the tracking of vibrational structural changes of reacting molecules with unprecedented temporal precision and spectral resolution while being technologically simple enough to be widely accessible and applicable.…" This and more about the story behind the front cover can be found in the Review at10.1002/cphc.201600104 .